Thermal-hydraulic analysis of a 7-pin sodium fast reactor fuel bundle with a new pattern of helical wire wrap spacer. (April 2018) - Park, Seong Dae; Seo, Han; Jeong, Yeong Shin; Jerng, Dong Wook; Bang, In Cheol
Highlights: A new type of arrangement for wire-wrapped spacers is presented to provide favorable flow for coolant mixing. The new pattern of wire spacer had 30 °C reduced temperature than ordinary ones. Pressure drop of the new type was reduced about 10% compared with the ordinary pattern. Abstract: Thermal-hydraulic analysis was performed with a 7-pin fuel bundle by using CFD. The ordinary wire-wrapped spacers are wound on the fuel pins in the same direction. Counter flow is predicted to occur in all sub-channels due to this pattern. This flow was confirmed in this analysis work. A new type of arrangement for wire-wrapped spacers, called the U-pattern, is presented to provide favorable flow for coolant mixing. In this pattern, 7 pins are designated in a group, the center pin has no wrapping spacer, and the pins surrounding the center pin have alternate winding directions of the spacer. Superior mixing effect and the uniform flow were confirmed in this pattern. This pattern has about 30 °C cooler than that of the ordinary wire-wrapped fuel bundle pattern in the maximum temperature region. Pressure drop of the U-pattern was reduced about 10% compared with the ordinary pattern. The new pattern of the fuel pins enhances the heat transfer and reduces pressure drop simultaneously.